2022
DOI: 10.1126/sciadv.abk1888
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and performance relevance of nanomorphogenesis in polyamide films revealed by quantitative 3D imaging and machine learning

Abstract: Biological morphogenesis has inspired many efficient strategies to diversify material structure and functionality using a fixed set of components. However, implementation of morphogenesis concepts to design soft nanomaterials is underexplored. Here, we study nanomorphogenesis in the form of the three-dimensional (3D) crumpling of polyamide membranes used for commercial molecular separation, through an unprecedented integration of electron tomography, reaction-diffusion theory, machine learning (ML), and liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 62 publications
2
44
0
Order By: Relevance
“… a The correlation coefficient R 2 , a common statistical parameter used for analyzing the linear dependence between a pair of variables, was obtained using Microsoft Excel software. This parameter has been commonly used for studying the membrane structure–property relationship in the literature. , b TEM-void fraction was calculated as the ratio between the area of the voids in the PA layer and the total area of the PA layer, where the areas were measured by the software Image pro plus based on the TEM micrographs. c TEM-apparent thickness was measured as the overall thickness of the crumpled nanovoid-containing PA layer using Image pro plus based on the TEM micrographs. d SEM-surface coverage was calculated as the ratio between the projected area of the exterior PA layer and the projected area of the total PA layer, where the areas were measured by Image pro plus based on the SEM micrographs. e AFM-RMS (root-mean-square roughness), AFM-average height, and AFM-surface area ratio were obtained by the AFM tests. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a The correlation coefficient R 2 , a common statistical parameter used for analyzing the linear dependence between a pair of variables, was obtained using Microsoft Excel software. This parameter has been commonly used for studying the membrane structure–property relationship in the literature. , b TEM-void fraction was calculated as the ratio between the area of the voids in the PA layer and the total area of the PA layer, where the areas were measured by the software Image pro plus based on the TEM micrographs. c TEM-apparent thickness was measured as the overall thickness of the crumpled nanovoid-containing PA layer using Image pro plus based on the TEM micrographs. d SEM-surface coverage was calculated as the ratio between the projected area of the exterior PA layer and the projected area of the total PA layer, where the areas were measured by Image pro plus based on the SEM micrographs. e AFM-RMS (root-mean-square roughness), AFM-average height, and AFM-surface area ratio were obtained by the AFM tests. …”
Section: Resultsmentioning
confidence: 99%
“… a The correlation coefficient R 2 , a common statistical parameter used for analyzing the linear dependence between a pair of variables, was obtained using Microsoft Excel software. This parameter has been commonly used for studying the membrane structure–property relationship in the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…Still, IP faces certain inherent limitations. Namely, the reaction is self-terminated so uncontrolled film growth can result in membranes with undesired thickness and rough surface morphology [13][14][15][16]. The properties of the support-layer surface can also lead to inconsistent polymerization behavior, with undesirable consequences to membrane performance [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the crumples exhibit different effective moduli depending on the morphology groups they belong to. 72 Despite the variety of crumples observed in the membrane (Fig. 3a), they consistently fall into these four groups; crumples within each group show high quantitative similarity in their fingerprints (Fig.…”
Section: Resultsmentioning
confidence: 91%